The Essence of Legal Research is to Resolve Legal Problems - Peter Machmudz Marzuki (Yuridika, 2022)
Legal research is carried out to resolve legal problems. Since jurisprudence is  a prescriptive science, legal research is conducted to produce prescription. The prescription may be the basis of resolving the legal problem. It is different from research for behavioral science or social research which is to verify a hypothesis. Data are needed to verify the hypothesis. On the other hand, legal research does not need data since it is not conducted to verify a hypothesis. Social research is to find coherence truth while, legal research is to discover coherence truth. Despite usage of induction in establishing argument, legal research does not use data to find the truth because the truth found is coherence truth. Legal research may be for practical purpose or for academic activity but is still like any other research and begins with problem, which  is a legal problem. Legal problems in  legal research should be clearly defined; otherwise, there will be misapplication of law to the problem. Consequently, the problem will not be solved. Legal problems may be causal relationship, functional relationship, or two propositions where the latter proposition gives clear meaning to the first proposition. The type of legal problem should be identified. It is necessary to collect legal research materials, which may be primary legal materials, secondary legal materials, and non-legal materials. The non-legal materials are supporting and complementary materials. Legal research may be carried out by using approaches as necessary. There are five types of approaches, statute approach, case approach, historical approach, comparative approach, and conceptual approach. The respective approach should be used appropriately.